Determination of the mesio-distal tooth width via 3D imaging techniques with and without ionizing radiation: CBCT, MSCT, and µCT versus MRI. (30th June 2016) - Detterbeck, Andreas; Hofmeister, Michael; Haddad, Daniel; Weber, Daniel; Schmid, Matthias; Hölzing, Astrid; Zabler, Simon; Hofmann, Elisabeth; Hiller, Karl-Heinz; Jakob, Peter; Engel, Jens; Hiller, Jochen; et al.
Summary: Objective: The purpose of this study was to estimate the feasibility and accuracy of mesio-distal width measurements with magnetic resonance imaging (MRI) in comparison to conventional 3D imaging techniques [multi-slice CT (MSCT), cone-beam CT (CBCT), and µCT]. The measured values of the tooth widths were compared to each other to estimate the amount of radiation necessary to enable orthodontic diagnostics. Material and Methods: Two pig skulls were measured with MSCT, CBCT, µCT, and MRI. Three different judges were asked to determine the mesio-distal tooth width of 14 teeth in 2D tomographic images and in 3D segmented images via a virtual ruler in every imaging dataset. Results: Approximately 19% (27/140) of all test points in 2D tomographic slice images and 12% (17/140) of the test points in 3D segmented images showed a significant difference ( P ≤ 0.05). The largest significant difference was 1.6mm ( P < 0.001). There were fewer significant differences in the measurement of the tooth germs than in erupted teeth. Conclusions: Measurement of tooth width by MRI seems to be clinically equivalent to the conventional techniques (CBCT and MSCT). Tooth germs are better illustrated than erupted teeth on MRI. Three-dimensional segmented images offer only a slight advantage over 2D tomographic slice images. MRI, which avoids radiation, is particularly appealing in adolescents if these data can be corroborated in further studies.